Produksi dan Laju Dekomposisi Serasah Daun Mangrove di Kawasan Wisata Mangrove Gununganyar Surabaya - Meisel Kristian Dui; Nirmalasari Idha Wijaya; Nor Sa'adah (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2022)
Mangrove litter has a very important function for the mangrove ecosystem, including to maintain the fertility of the forest soil in question. This study aims to determine the production and rate of decomposition in the Gununganyar Mangrove Tourism Area. The study was conducted by installing a litter net or litter-trap as a container for fallen mangrove leaves, this was done to determine the productivity of mangrove leaf litter, litter collection on the litter-trap was carried out for 1 month and was taken at 30-day intervals and installed a litter-bag for placing mangrove leaf litter. The litter production at Station 1, Station 2 and Station 3 was 194.976 kg/ha/month, 681.84 kg/ha/month, 925.275 kg/ha/month. The results of the litter decomposition rate in the Gununganyar Mangrove Tourism Area from Station 1, Station 2, and Station 3 were 97.95%, 60.35% and 89.25%, respectively.